Shining a Light on Firms’ Political Connections: The Role of Dark Money - Denes, Matthew; Scanlon, Madeline Marco (The Review of Corporate Finance Studies, 2025)
We study the emergence of a new channel for firms’ political activity using dark money through undisclosed and unlimited contributions. After the U.S. federal court decisions in 2010, S&P 500 firms substantially increased their use of dark money. We find that dark money contributions complement political engagement through campaign contributions and lobbying. Firms disclose dark money contributions when they face heightened nondisclosure costs. Firms contributing to dark money groups benefit by receiving more procurement contracts and increased government subsidies. Our findings highlight that political connections by firms are evolving and expanding through new and largely unexplored channels. (JEL D72, D73, G38, H57)